The Relationship Between the Modulation of Intestinal Microbiota and the Response to Immunotherapy in Patients with Cancer - Laura Radoš; Marin Golčić; Ivana Mikolašević (Biomedicines)
The intestinal microbiota is an important part of the human body, and its composition can affect the effectiveness of immunotherapy. In the last few years, the modulation of intestinal microbiota in order to improve the effectiveness of immunotherapy has become a current topic in the scientific community, but there is a lack of research in this area. In this review, the goal was to analyze the current relevant literature related to the modulation of intestinal microbiota and the effectiveness of immunotherapy in the treatment of cancer. The effects of antibiotics, probiotics, diet, and fecal microbial transplantation were analyzed separately. It was concluded that the use of antibiotics, especially broad-spectrum types or larger quantities, causes dysbiosis of the intestinal microbiota, which can reduce the effectiveness of immunotherapy. While dysbiosis could be repaired by probiotics and thus improve the effectiveness of immunotherapy, the use of commercial probiotics without evidence of intestinal dysbiosis has not yet been sufficiently tested to confirm its safety for cancer for immunotherapy-treated cancer patients. A diet consisting of sufficient amounts of fiber, as well as a diet with higher salt content positively correlates with the success of immunotherapy. Fecal transplantation is a safe and realistic adjuvant option for the treatment of cancer patients with immunotherapy, but more clinical trials are necessary. Modulating the microbiota composition indeed changes the effectiveness of immunotherapy, but in the future, more human studies should be organized to precisely determine the types and procedures of microbiota modulation.